Phase 1b trial of docetaxel, prednisone, and pazopanib in men with metastatic castration‐resistant prostate cancer. Issue 15 (9th September 2019) - George, Daniel J.; Halabi, Susan; Healy, Patrick; Barak, Ian; Winters, Carolyn; Anand, Monika; Wilder, Rhonda; Klein, Melissa; Martinez, Elia; Nixon, Andrew B.; Harrison, Michael R.; Szmulewitz, Russell; et al.
Abstract: Background: Docetaxel prednisone is a standard of care for men with metastatic castration‐resistant prostate cancer (mCRPC), and plasma vascular endothelial growth factor (VEGF) levels are a poor prognostic factor in this population; therefore, we evaluated the combination of docetaxel prednisone with pazopanib, an oral VEGF receptor inhibitor, for safety and preliminary efficacy. Methods: This is a two‐site phase 1b Department of Defense Prostate Cancer Clinical Trials Consortium trial of docetaxel, prednisone, and pazopanib once daily and ongoing androgen deprivation therapy and prophylactic pegfilgrastim in men with mCRPC. The primary endpoint was safety and the determination of a maximum tolerated dose (MTD) through a dose‐escalation and expansion design; secondary endpoints included progression‐free and overall survival (OS), prostate specific antigen (PSA) declines, radiographic responses, and pharmacokinetic and plasma angiokine biomarker analyses. Results: Twenty‐five men were treated over six dose levels. Pegfilgrastim was added to the regimen after myelosuppression limited dose escalation. With pegfilgrastim, our target MTD of docetaxel 75 mg/m 2 q3 weeks; prednisone 10 mg daily; and pazopanib 800 mg daily was reached. Eleven additional patients were accrued at this dose level for a total of 36 patients. Dose‐limiting toxicities included neutropenia, syncope, and hypertension. Three deaths attributed to study treatment occurred. The objective response rate was 31%; median PFS was 14.1 months (95% confidence interval [CI]: 7.1 and 22.2); and OS was 18.6 months (95% CI: 11.8 and 22.2). Conclusions: The combination of docetaxel, prednisone, and pazopanib (with pegfilgrastim) was tolerable at full doses and demonstrated promising efficacy in a relatively poor risk patients with mCRPC. Further development of predictive biomarkers may enrich for patients who receive clinical benefit from this regimen.